Initial clinical experience with the ADAPT technique: A direct aspiration first pass technique for stroke thrombectomy. (27th April 2013) - Turk, Aquilla S; Spiotta, Alex; Frei, Don; Mocco, J; Baxter, Blaise; Fiorella, David; Siddiqui, Adnan; Mokin, Maxim; Dewan, Michael; Woo, Henry; Turner, Raymond; Hawk, Harris; et al.
Abstract : Background: The development of new revascularization devices has improved recanalization rates and time but not clinical outcomes. We report our initial results with a new technique utilizing a direct aspiration first pass technique with a large bore aspiration catheter as the primary method for vessel recanalization. Methods: A retrospective evaluation of a prospectively captured database of 37 patients at six institutions was performed on patients where the ADAPT technique was utilized. The data represent the initial experience with this technique. Results: The ADAPT technique alone was successful in 28 of 37 (75%) cases although six cases had large downstream emboli that required additional aspiration. Nine cases required the additional use of a stent retriever and one case required the addition of a Penumbra aspiration separator to achieve recanalization. The average time from groin puncture to at least Thrombolysis in Cerebral Ischemia (TICI) 2b recanalization was 28.1 min, and all cases were successfully revascularized. TICI 3 recanalization was achieved 65% of the time. On average, patients presented with an admitting National Institutes of Health Stroke Scale (NIHSS) score of 16.3 and improved to an NIHSS score of 4.2 by the time of hospital discharge. There was one procedural complication. Discussion: This initial experience highlights the fact that the importance of the technique with which new stroke thrombectomy devices are used may be as crucial as the device itself. The ADAPT technique is a simple and effective approach to acute ischemic stroke thrombectomy. Utilizing the latest generation of large bore aspiration catheters in this fashion has allowed us to achieve excellent clinical and angiographic outcomes.